Strategie wygrywające w teorii i praktyce - Malara, Zbigniew (Winning Strategies in Theory and Practice, 2008)
The main aim of the paper is to discover theoretical and practical prerequisites and solutions used in forming and implementing the winning strategies. The rudimental premises of formulating strategies in the global context of economy and key conditions in their implementation are presented. The role and meaning of the chain value and its elements are described too. The source of strategies and their types are presented as well. Finally, the model of business and the features of its functioning are discussed. In conclusion, the paradigm of inconstancy (changing) the enterprise's success and the necessity of searching the new solutions and sources, useful in formulating the winning strategies of contemporary enterprise, are precised.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 216-226